Feminist Methodologies for Gender Studies Teaching: Cross-Case Analysis of Practical Applications in Three Universities - Werner, Ann; Novelskaitė, Aurelija; Lukovitskaya, Elena (Information & Media, 2023)
In this article interpersonal communication in Gender Studies teaching is mapped and compared in feminist pedagogy in three universities: Södertörn University in Sweden, Novgorod State University in Russia and Vilnius University in Lithuania. The aim of this article is, first, to compare the uses of feminist methodologies in teaching during the first semester undergraduate Gender Studies courses in a cross-case comparison. And secondly, to suggest developments needed to pursue teaching in Gender Studies in the three countries. Scholarly discussions about feminist pedagogies are accounted for and characteristics from the field are identified and compared in the three empirical cases. The article further draws on qualitative feminist methodology and concludes that while the contexts investigated are different, the methodologies used have similarities. In all three universities the teaching methods focus on students’ experiences and differences, teacher’s reflexivity, working in smaller groups, highlighting community building and empowerment. In the conclusion these teaching holdings are discussed, and further development of interpersonal communication in Gender Studies teaching is suggested.